2021
DOI: 10.3389/fimmu.2021.726920
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a Fusion Polyprotein Based on HspX and Other Antigen Sequences for the Serodiagnosis of Tuberculosis

Abstract: BackgroundThe lack of suitable diagnostic tools contributes to the high prevalence of tuberculosis (TB) worldwide. Serological tests, based on multiple target antigens, represent an attractive option for diagnosis of this disease due to their rapidity, convenience, and low cost.MethodsMeasures to reduce non-specific reactions and thereby improve the specificity of serological tests were investigated, including blocking antibodies against common bacteria in serum samples and synthesizing polypeptides covering n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Although an effective Th1-type cell-mediated adaptive immune response characterized by the secretion of IFN-γ and TNF via antigen-specific CD4 T cells is known to be required, it is not sufficient to provide protective immunity against TB. For example, numerous studies indicated that humoral immunity also plays an important role in anti-TB immunity [ 35 , 36 , 37 ]. In view of the complexity of TB–host interactions, the mechanism related to the immune response to TB is still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Although an effective Th1-type cell-mediated adaptive immune response characterized by the secretion of IFN-γ and TNF via antigen-specific CD4 T cells is known to be required, it is not sufficient to provide protective immunity against TB. For example, numerous studies indicated that humoral immunity also plays an important role in anti-TB immunity [ 35 , 36 , 37 ]. In view of the complexity of TB–host interactions, the mechanism related to the immune response to TB is still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there is a renewed effort to improve on serodiagnosis of TB by either combining different tests (4), or combining multiple antigens or epitopes of Mtb (4)(5)(6)(7)(8)(9)(10)(11)(12), with some of the reports claiming discriminatory potential between active TB and LTBI (6,7,9,10). In this study, we performed an exploratory study on a historic set of serum samples from TB patients, LTBI and healthy (BCG vaccinated) controls in Mozambique, collected between 2016 and 2018 as part of a wider study [ (13,14) the EMI-TB project].…”
Section: Introductionmentioning
confidence: 99%